Doing “well” or doing “good” : what audience analytics reveal about journalism’s competing goals - Nelson, Jacob L. (2020)
Journalism research frequently takes the form of ethnographic case studies. Because ethnographic data collection tends to be limited to months or even weeks, these studies are often unable to uncover how journalism changes over time. Our study addresses this gap by drawing on ethnographic data collected from a large, metropolitan newspaper in 2013 and again in 2016. In doing so, it answers the question: How has a newspaper’s relationship with online audience analytics changed? Our findings show that audience metrics continue to play an important role in the news production process. However, the adoption of online metrics has been less universal and deliberate than the paper’s staff originally assumed it would be. Drawing on market information regime and normalization literature, we conclude that ambivalence about these analytics has made explicit the idea that journalists face two goals they perceive as mutually exclusive: the pursuit of a mass audience and the aspiration to provide mission-driven reporting.